INFLUENCE OF CURRENT RATIO, DEBT TO EQUITY RATIO, TOTAL ASSET TRUN OVER, RETURN ON EQUITY, AND EARNING PER SHARE AGAINST COMPANY STOCK PRICE (STUDY OF LQ 45 PERIOD 2014-2016). - MAYANTI, ROI (Jurnal Ilmiah Mahasiswa FEB, 2018)
This research aims to help investors in deciding how to invest in the stockmarket by analyzing the impact of company’s financial ratio on its share price. Financial Ratio used in this research are Current Ratio, Debt-Equity Ratio, Total Asset Turnover, Return on Equity, and Earning per Share as independent variables, and Stock Price as the dependent variable. This research employed the purposive sampling method using 28 samples of LQ45 companies which fulfilled the research criteria between 2014 – 2016 from 45 existing listed companies. This research employed Multiple Linear Regression analysis to test the hypothesis. The result shows that the Total Asset Turnover and Earning per Share have significant influence on Stock Price, whereas Debt Equity Ratio, and Return on Equity do not have significant influence on stock price. Investors should review financial statements issued by the company and use financial ratios particularly Current Ratio, Total Asset Turnover and Earning per Share (EPS) as references in making an investment. KeywordsKeywords: Current Ratio, Debt Equity Ratio, , Return on Equity and Earning per Share, Stock Price.